33‐3: Display Panel Certification System for the Vehicle Industry. Issue 1 (May 2017) - Hermann, David; Djupsjöbacka, Anders; Andrén, Börje; Brunnström, Kjell; Rydell, Niclas
Abstract : The ever‐increasing need for displaying in‐vehicle visual information in a non‐distracting way requires a high visual performance of automotive displays. For their procurement, deep technical and supply‐chain knowledge is required. Therefore, based on our comparisons of in‐vehicle and laboratory visual‐performance measurements, we propose a certification system for automotive display panels.